2021
DOI: 10.1002/micr.30775
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center retrospective comparison of Duplex ultrasonography versus audible Doppler regarding anterolateral thigh perforator flap harvest and operative times

Abstract: Introduction:We reported on the superiority of preoperative Duplex mapping ("Duplex") over audible Dopplers ("Doppler") in anterolateral thigh perforator (ALT) free flaps for upper extremity reconstruction. To corroborate our findings on a larger cohort, we conducted this present study focusing on surgical efficiency and patient safety.Methods: 150 consecutive ALT free flaps were divided into 65 cases of preoperative Duplex versus 85 Doppler controls. We first compared patient demographics, operative details, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
2
4
0
1
Order By: Relevance
“…By providing detailed information on perforator location and course, surgeons can proceed with the operation within the predicted range, potentially reducing the time required for flap elevation. Our findings can be interpreted in the context of previous studies (Thomas et al, 2020; Thomas et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…By providing detailed information on perforator location and course, surgeons can proceed with the operation within the predicted range, potentially reducing the time required for flap elevation. Our findings can be interpreted in the context of previous studies (Thomas et al, 2020; Thomas et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…A comparable preoperative use of the investigated Doppler transducer to detect certain blood vessels had been reported in the field of reconstructive antero-lateral thigh flap surgery in several T A B L E 2 Mean and median distances between the centre of the detected signal and the gingival margin on the right side. studies (Cheng et al, 2012;Lethaus et al, 2017;Thomas et al, 2020Thomas et al, , 2022. We found that it was possible to detect a clear arterial pulse signal in at least 80%-90% of all measurements within the clinically most relevant palatine molar and premolar regions.…”
Section: Discussionmentioning
confidence: 69%
“…As an example, in the context of surgical interventions, Doppler techniques are commonly used in thigh‐flap surgery. In particular, the preoperative detection of perforating blood vessels in antero‐lateral thigh‐flap surgery has been reported in multiple studies (Cheng et al, 2012; Lethaus et al, 2017; Thomas et al, 2020, 2022). In these studies, both colour‐coded duplex ultrasonography and an 8‐MHz handheld DUS transducer were successfully used.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to surgery, ALT perforator mapping was performed by marking and scanning both thighs on the eve of operation as described elsewhere (Thomas et al, 2020; Thomas, Haug, et al, 2021): in brief, anatomic landmarks were identified, including the intermuscular septum between the anterior superior iliac spine and superolateral patella. At its midpoint, suitable perforators were then located and marked by using either unidirectional audible Doppler probes or linear multifrequency transducers with overlaid B‐ and Color‐Flow‐modes.…”
Section: Methodsmentioning
confidence: 99%